An Analysis of Figurative Language Used in Nine Track Mind Album by Charlie Puth - Sintana Novita Dewi; Ida Ayu Putri Gita Ardiantari (CV Wahana Publikasi, 2024)
In writing songs, songwriters often use figurative language. This research analyzed the figurative language in the album Nine Track Mind by Charlie Puth. This research aimed to determine the type of figurative language used and the meaning shown by figurative language in the songs on the album. This research is descriptive research with qualitative and quantitative approaches. The data found in this research were analyzed by the theory of Knickerbocker and Reninger (1963) and supported by the theory of Wellen and Warren (1984). This research showed that songwriters used ten figurative language, namely 60% hyperbole, 10% allusion, 10% repetition, and 20% metaphor. In addition, the songwriter also uses connotative and denotative meanings in the album.